Characteristics of HIV-1-associated Kaposi's sarcoma among women and men in South Africa. - Mosam, A; Hurkchand, H P; Cassol, E; Page, T; Cassol, S; Bodasing, U; Aboobaker, J; Dawood, H; Friedland, G H; Coovadia, H M (International journal of STD & AIDS, 2008)
Despite the increase of HIV-1-associated Kaposi's sarcoma (KS), little is known about HIV-associated KS in the African setting, particularly among women. A descriptive study of the demographic, clinical, immunological and virological features of AIDS-associated KS from KwaZulu-Natal, South Africa was undertaken. Consecutively, recruited patients were clinically staged; CD4/CD8 cell counts, HIV-1 viral loads and clinical parameters were evaluated. Of the 152 patients (77 male and 75 female) 99% were black. Females were significantly younger (P = 0.02) and had poorer disease prognosis (odds ratio [OR] = 2.7, 95% confidence interval [CI] = 1.4-5.4, P = 0.003) and were more likely to have extensive cutaneous KS when compared with males (OR = 3.1, 95% CI = 1.4-6.7, P = 0.003). One-third of patients had coexisting HIV-related disease, most commonly tuberculosis, and these were more frequent in females (56.7 vs. 43.3%). In conclusion, HIV-associated KS in South Africans has an equal female-to-male ratio. Females are younger and have more severe disease than males.
Keywords: Adult; AIDS-Related Opportunistic Infections; CD4 Lymphocyte Count; Cross-Sectional Studies; Female; HIV Infections; HIV Seropositivity; HIV-1; Humans; Male; Sarcoma, Kaposi; South Africa